The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/su9091662
|View full text |Cite
|
Sign up to set email alerts
|

Differences of Cycling Experiences and Perceptions between E-Bike and Bicycle Users in the United States

Abstract: E-bikes are bicycles that provide pedal-assistance to aid people in cycling. Because of the potential of promoting sustainable transportation, more attention has been focused on the e-bike market. This paper investigates the differences of the cycling experience and perceptions between e-bike and conventional bicycle users, using samples drawn from independent bicycle dealer customers. A total of 806 respondents in the United States took the on-line survey, including 363 e-bike-owning respondents. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 36 publications
3
38
0
Order By: Relevance
“…The similarities between motorcycle and bicycle may cause a little promotive relation between them. Finally, it is interesting to see that e-bicycle and bicycle are also mutually promotive, as shown by the positive correlation (0.0273), although the correlation is very small, possibly due to the similarity between e-bicycle and bicycle on the aspect of flexibility and sustainability [50].…”
Section: Discussion On Error Correlation Matrixmentioning
confidence: 97%
“…The similarities between motorcycle and bicycle may cause a little promotive relation between them. Finally, it is interesting to see that e-bicycle and bicycle are also mutually promotive, as shown by the positive correlation (0.0273), although the correlation is very small, possibly due to the similarity between e-bicycle and bicycle on the aspect of flexibility and sustainability [50].…”
Section: Discussion On Error Correlation Matrixmentioning
confidence: 97%
“…Fishman and Cherry [13] provided a comprehensive review on e-bike-related literature, whose focus is transport instead of recreational e-bike research. E-bikes were shown to reduce the fatigue level [14][15][16][17] and increase the cyclist's mode satisfaction level [18]. It was also found that e-bikes can increase the ridership or travel distance in comparison with traditional bikes [4,15,19,20].…”
Section: Related Workmentioning
confidence: 96%
“…Equations (13) and (14) ensure that the same fleet deployment plan is applied at the initial period of planning horizon for different demand realisations. Constraints (15) and (16) are balancing constraints for the number of bikes and e-bikes at the beginning of each period t. Constraint (17) ensures that the number of bikes at each station can never exceed the capacity of bike station; constraint (18) ensures that the number of e-bikes at each e-bike station cannot exceed the total number of charging piles. Equations (19) and (20) are fleet size constraints to ensure that the total fleet size in each demand scenario is the same, and the fleet size constraint can also serve as a budget constraint.…”
Section: Upper-level Modelmentioning
confidence: 99%
“…Hence, the space of the investigated problem is equal to 8. Based on [69][70][71][72][73][74][75][76][77][78][79][80], the following criteria are specified: [74,79].…”
Section: Study Casementioning
confidence: 99%